2023
DOI: 10.1038/s41526-023-00295-y
|View full text |Cite
|
Sign up to set email alerts
|

Paving the way to better understand the effects of prolonged spaceflight on operational performance and its neural bases

A. C. Stahn,
D. Bucher,
P. zu Eulenburg
et al.

Abstract: Space exploration objectives will soon move from low Earth orbit to distant destinations like Moon and Mars. The present work provides an up-to-date roadmap that identifies critical research gaps related to human behavior and performance in altered gravity and space. The roadmap summarizes (1) key neurobehavioral challenges associated with spaceflight, (2) the need to consider sex as a biological variable, (3) the use of integrative omics technologies to elucidate mechanisms underlying changes in the brain and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Over the course of the last five to six decades, there has been considerable work trying to understand how spaceflight (radiation and microgravity) affects living systems, with special interest in human medicine [1][2][3] . Studies have shown that the spaceflight environment induces elevated CO2-levels and regional hypoxia in the human brain 2 , which has been linked to lower gray matter volume and changes in vestibular connectivity 4 . Spaceflight can also affect red blood cell mass through a process called 'neocytolysis', which selectively leads to hemolysis of young circulating red blood cells 5,6 .…”
Section: Human Respiratory Health In Spaceflightmentioning
confidence: 99%
“…Over the course of the last five to six decades, there has been considerable work trying to understand how spaceflight (radiation and microgravity) affects living systems, with special interest in human medicine [1][2][3] . Studies have shown that the spaceflight environment induces elevated CO2-levels and regional hypoxia in the human brain 2 , which has been linked to lower gray matter volume and changes in vestibular connectivity 4 . Spaceflight can also affect red blood cell mass through a process called 'neocytolysis', which selectively leads to hemolysis of young circulating red blood cells 5,6 .…”
Section: Human Respiratory Health In Spaceflightmentioning
confidence: 99%
“…Today, space exploration missions move from low orbit to distant destinations, including the Moon and Mars. These will inevitably face new challenges that will include not only neurobehavioural 5 but also more psychological aspects. 6 …”
Section: Introductionmentioning
confidence: 99%
“…As a species, we have been working and living in space for more than 60 years, with continuous occupation for the last 23 years via the International Space Station (ISS) [1]. During this time, we have discovered that spaceflight induces numerous physiologic alterations, including but not limited to muscle and bone loss, structural changes in the eyes and brain, altered cardiovascular function, and altered cognitive function [2][3][4][5][6][7][8][9]. In some cases, we have developed effective countermeasures for these undesirable outcomes, but in other cases, understanding and countering the causes of these outcomes remain active areas of investigation.…”
Section: Introductionmentioning
confidence: 99%